SYMPTOMS AND DIAGNOSIS OF HIRSCHSPRUNG’S DISEASE - Putu Ayu Ines Lassiyani Surya; I Made Dharmajaya (Universitas Udayana, 2014)
Hirschsprung disease is a disease that attacks the human digestive system, mainly in the largeintestine (colon). In this disease, found enlargement of the colon (megacolon), due to the absenceof ganglion cells in the distal intestine. Hirschsprung disease often affects neonates and evenchildren, are often characterized by delays in spending the first meconium, bilious vomiting,abdominal distension. Methods diagnois do for Hirschsprung's disease was confirmed by biopsy,barium enema or contrast enema, and anorectal manometry. Early diagnosis is crucial to conductrapid and appropriate treatment and to prevent complications.